Kebijakan Fiskal Dalam Perspektif Ekonomi Islam Serta Relevansinya Di Negara Indonesia - Moh Fitra Febriana; Setia Mulyawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In classical discourse, Islamic governments that have appeared on the stage of history have exemplified the forms of state income and expenditure. This article describes a comparison of fiscal policy, namely in the income and expenditure of the state treasury according to Islamic and conventional government systems and their implementation which has similarities with fiscal policy in Indonesia. The study method used is literature study, the data obtained is compiled, analyzed and concluded to draw conclusions. The results of the study show that fiscal policy has been implemented since the time of the Prophet Muhammad with the emergence of policy instruments that are in accordance with Islamic principles. As for the fiscal policy that has been exemplified in Islamic government, it has been able to be reformulated in accordance with the legal order and culture of the Indonesian people. It's just that the implementation mechanism is different from what has been implemented by Islamic governments, however, the principles and objectives have much in common. As for the fiscal policies of the State of Indonesia which are considered to be adapted from the Islamic government system, namely kharaj with PBB, 'usyr such as customs with PPn and jizyah such as visas with PPh.